Assessment of Risk Factors Associated with Surgical Site Infection Following Elective Gastrointestinal Surgery: A Prospective Cohort Study - Dr. Anil U. S., Dr. Maheboob Pasha, Dr. Sachin C. A, (International Journal of Pharmacy Research & Technology (IJPRT), 2026)
Background: Surgical site infection (SSI)remains the most common health-care–associatedinfection after gastrointestinal (GI) surgery andcontinues to prolong hospitalisation and increasecosts, particularly in low- and middle-income settings. Robust local data on modifiable